Frequency of Kidney Cancer in Nephrectomy Specimens in Different Hospitals in Dhaka Bangladesh – a Retrospective Study (Bangladesh Journal of Urology, 2020)
Background: Kidney cancer is uniformly lethal once the tumor extends beyond Fascia Gerota. But if diagnosed early surgery provides excellent results with regard to local disease control and prospect for long term disease free survival.Objective : To assess the frequency of kidney cancer among the submitted kidney tissue for histopathological examination.Method: This analytical retrospective observational study of 550 histopathological reports of nephrectomy specimen was done in different hospitals and institute in Dhaka city. Histopathology reports from January 2007 to December 2009 were collected and all data are compiled and analysed using SPSS version 16 and appropriate statistical tests were done to make inference.Results : During the study period, among the 550 histopathological specimen of kidney tissue, RCC was found to be most common type 201(36.5%), TCC renal pelvis was 41(7.5 %), Wilms tumor 54(9.8%) and sarcoma 5 (0.9%) and rest were benign. Among the 201 cases RCC only in 130 cases tumor grade was mentioned, with grade II most common type. Peak age group of kidney cancer was found to be 4th decade and no cancer was found between 10 to 30 years of age. Wilms tumor became most common child hood renal malignancy with mean age 7 years.Conclusion: The results of the study shows kidney cancer, the most lethal of the urologic cancer is not a common cancer in our country .The most affected age group is 5th decade younger than western countries. RCC is the most common type found and males are affected almost twice than female. National cancer registry should be opened and proper entry should be ensured.Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.83-87